Herpes Simplex Keratitis - Kaye, Stephen; Choudhary, Anshoo (Progress in Retinal and Eye Research, 2006)
Herpes simplex keratitis (HSK) results from an infection with the herpes simplex virus type 1 (HSV-1) also known as human herpesvirus type 1 (HHV-1). Primary infection may involve an ocular or non-ocular site, following which latency might be established principally in the trigeminal ganglion but also in the cornea. During latency, the virus appears as a circular episome associated with histones with active transcription only from the region encoding the latency-associated transcript (LAT). The LAT region is implicated in neuronal survival, anti-apoptosis, virulence, suppression of transcription, establishment of and reactivation from latency. The initial keratitis may develop after infection through the ‘‘front door route’’ (entry into the ocular surface from droplet spread) or ‘‘back door route’’ (spread to the eye from a non-ocular site, principally the mouth). The initial ocular infection may be mild. Visual morbidity results from recurrent keratitis, which leads to corneal scarring, thinning and neovascularisation. Although, recurrent disease may potentially occur through anterograde axonal spread from the trigeminal ganglion to the cornea, recent evidence suggests that HSV-1 in the cornea may be another source of recurrent disease. The pathogenesis and severity of HSK is largely determined by an interaction between viral genes encoded by the strain of HSV-1 and the make up of the host’s immune system. Herpetic stromal disease is due to the immune response to virus within the cornea and the ability of the strain to cause corneal stromal disease is correlated with its ability to induce corneal vascularisation. The pathogenesis of corneal scarring and vascularisation is uncertain but appears to be a complex interaction of various cytokines, chemokines and growth factors either brought in by inflammatory cells or produced locally in response to HSV-1 infection. Evidence now suggests that HSV-1 infection disrupts the normal equilibrium between angiogenic and anti-angiogenic stimuli leading to vascularisation. Thrombospondin 1 and 2, matricellular proteins, involved in wound healing are potent anti-angiogenic factors and appear to be one of the key players. Elucidating their roles in corneal scarring and vascularisation may lead to improved therapies for HSK.